Peptides and Food Intake - Sobrino Crespo, Carmen; Perianes Cachero, Aránzazu; Puebla Jiménez, Lilian; Barrios, Vicente; Arilla Ferreiro, Eduardo (Frontiers in Endocrinology, 2014)
Nutrients created by the digestion of food are proposed to active G protein coupled receptors on the luminal side of enteroendocrine cells e.g. the L-cell. This stimulates the release of gut hormones. Hormones released from the gut and adipose tissue play an important rol in the regulation of food intake and energy expenditure (1). Many circulating signals, including gut hormones, can influence the activity of the arcuate nucleus (ARC) neurons directly, after passing across the median eminence. The ARC is adjacent to the median eminence, a circumventricular organ with fenestrated capillaries and hence an incomplete blood-brain barrier (2). The ARC of the hypothalamus is believed to play a crucial role in the regulation of food intake and energy homeostasis. The ARC contains two populations of neurons with opposing effect on food intake (3). Medially located orexigenic neurons (i.e those stimulating appetite) express neuropeptide Y (NPY) and agouti-related protein (AgRP) (4-5). Anorexigenic neurons (i.e. those inhibiting appetite) in the lateral ARC express alpha-melanocyte stimulating hormone (α-MSH) derived from pro-opiomelanocortin (POMC) and cocaine and amphetamine-regulated transcript (CART) (6). The balance between activities of these neuronal circuits is critical to body weight regulation. In contrast, other peripheral signals influence the hypothalamus indirectly via afferent neuronal pathway and brainstem circuits. In this context gastrointestinal’s vagal afferents are activated by mechanoreceptors and chemoreceptors, and converge in the nucleus of the tractus solitaries (NTS) of the brainstem. Neuronal projections from the NTS, in turn, carry signals to the hypotalamus (1, 7). Gut hormones also alter the activity of the ascending vagal pathway from the gut to the brainstem. In the cases of ghrelin and Peptide tyrosine tyrosine (PYY), there are evidences for both to have a direct action on the arcuate nucleus and an action via the vagus nerve a